Use Google Sites to Increase Interest Learning Geography High School in Sukoharjo - Lilis Suparti Suparti; Poni Poni Poni; Pranichayudha Rohsulina Rohsulina (Journal of Geography Science and Education, 2021)
Distance learning geography at one Tawangsari State High School uses the Google classroom, which still has several shortcomings that make learning geography less interesting. Increase interest in learning geography using Google Sites learning media. The research method used descriptive research method with a quantitative approach. The data collection technique used by giving tests and observations. giving pretest and posttest, for data analysis the post test is used. Observation is used to collect data on student activities in accessing google sites. Learning is considered successful if the learning outcomes of students with the provision that at least 80% of students in one class reach the minimum completeness criteria, namely 75. The results of student observations in accessing learning media google sites can be seen that from 36 students, very good information there are 19 students with a percentage of 53% then increase in posttest test results by 11 students who completed with a percentage of 31% increased to 32 students who completed with a percentage of 89%. So it that google sites-based learning media can increase the learning interest of eleventh grade Social Sciences three students learning geography at  one Tawangsari State High School in 2021.